Comportamientos sexuales en la adolescencia - Bohórquez Pacheco, Juan Sebastián (2017)
This dissertation is presented in two articles derived from the same project about sexuality in the adolescence. The first article explain the descriptive behaviors of sexuality in a group of 560 adolescents from the city of Porto Alegre, Brazil. This part examines the behaviors and characteristics related to sexual initiation, the partner of the first sexual encounter, protection, and family orientation, as well as the parent’s responses to the sexual initiation of the adolescents. Among the results, we found that the means of the age of the first relation was 14.81 years; 82.1% was report uses of contraception at the first sexual intercourse; 60% of the parents know about the sexual life of his children and 72.3% of parents gave advice and guide young people about responsible sexual behavior. The second article discusses the sexual risk behaviors and gender differences presented by 365 adolescents who have already started their sexual life. The risk behaviors were: the age of sexual initiation, age difference with sexual partner, the frequency of condom use, use of contraceptives, number of partners in the last year and the history of pregnancies. Results indicated that 39.6% of this sample started their sexual activity between 14 and 15 years old; 69.8% of adolescents have until two years apart with their sexual partner; 52.6% use condoms in all their sexual relations; 54.2% use effective contraceptive methods; 60.3% have until two sexual partners in the last year and only 3.9% have a history of pregnancies. This result allow understand and describe the sexual behaviors in adolescence. In addition, the data provide empirical bases for the elaboration of projects and policies for the improvement of the health and prevent sexual risk behaviors.